Informal workers and access to healthcare: a qualitative study of facilitators and barriers to accessing healthcare for beer promoters in the Lao People’s Democratic Republic - Sychareun, Vanphanom (Int J Equity Health, 2016)
BACKGROUND: Informal workers often face considerable risks and vulnerabilities as a consequence of their work and employment conditions. The purpose of this study was to examine the interplay between the experience of informal work and access to health, using as an example, female beer promoters employed in the informal economy, in the Lao People’s Democratic Republic. METHODS: In-depth interviews were undertaken with 24 female beer promoters working in beer shops, restaurants and entertainment venues in Vientiane City. The recruitment strategy of snowball sampling was used. Interviews explored the beer promoter’s experience of the organization of work, perceived healthcare needs, access to healthcare and insurance, and health seeking practices. The data was analysed thematically and subsequently using Bourdieu’s concepts of habitus, capital and field. RESULTS: Most of the beer promoters included in the study were 18 years of age, single, had worked as beer promoters for more than one year and just over half were working to support their higher education. The beer promoters demonstrated a holistic view of health, also viewing good health as contributing to being beautiful – an important attribute in their work. Many reported that their work conditions, including the noisy environment, exposure to second-hand tobacco smoke, long hours on their feet and sexual harassment negatively affected their physical and mental health. Only four participants had any form of health insurance with access to healthcare constrained by individual characteristics, health system factors and the conditions of their informal employment. CONCLUSIONS: Drawing on the work of Bourdieu, the study shows how both employment and illness are linked to habitus embodied in everyday practices, access to capital and the position the female beer promoters hold in the social hierarchy in the field of employment.